O direito à educação de crianças de 0 a 3 anos e o espaço da creche: representações sociais de estudantes do curso de Pedagogia - Stanich, Karina Alves Biasoli (2018)
In Brazil, the Federal Constitution of 1988, together with the Law on Guidelines and Bases (Law 9.394 / 1996), constituted the first initiatives for the construction of a public policy that would ensure, among social and fundamental rights, the Education of children from 0 to 3 years old in daycare center/nurseries. Covered by the status of subjective public law, of a universal character, equated with the right to life and freedom, the right to education of children from 0 to 3 years old has become legally enforceable in cases of non-offer or non-regular offer by the competent public entity. In spite of the legal innovations, what happened in practice was a mismatch of the normative aspects and the real conditions of the public equipment that could not even meet the demand for access. Considering that Law is configured as a scientific knowledge that carries a symbolic dimension, it is verified that its effectiveness is conditioned to the struggles and negotiations undertaken through communication in the social sphere. Moreover, such communications involve specific concepts about their ownership that include conceptions of children, education and representations about the role of the family and the very space of the daycare center/nursery that may differ according to the group and their spatio-temporal insertion. Based on the theoretical and methodological contribution of the theory of social representations, the present study had as objective to offer an explanatory frame about the way in which the students of the Pedagogy course, of a university situated in the city of São Paulo, understood and represented the right to education of children from 0 to 3 years old, as well as the daycare center/nursery space. Data was gathered through the application of three instruments: a questionnaire/survey to find out the participants’ profile; another questionnaire/survey containing open questions with the aim of capturing students’ opinions on the objects entitled to “education” and “daycare center/nursery”; and a third questionnaire/survey, composed of three scenarios designed in the form of problem-situations in order to capture the representations of these students from the three dimensions that constitute a social representation: information, image and attitude. For the systematization and analysis of the data collected, the content analysis procedure was used. The results indicated that there is no representation built by this group of students on the right to education of children from 0 to 3 years old, but there are other representational families that are articulated around the concept of education, the role assigned to families and to the space itself of daycare center/nursery